2022
DOI: 10.1155/2022/4472751
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Torreya grandis Kernel Oil on Lipid Metabolism and Intestinal Flora in C57BL/6J Mice

Abstract: Background. Recent experimental studies have shown that vegetable oil supplementation ameliorates high-fat diet- (HFD-) induced hyperlipidemia and oxidative stress in mice via modulating hepatic lipid metabolism and the composition of the gut microbiota. The aim of this study was to investigate the efficacy of the Torreya grandis kernel oil (TKO) rich in unpolysaturated fatty acid against hyperlipidemia and gain a deep insight into its potential mechanisms. Methods. Normal mice were randomly divided into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…These studies suggest the potential for RBPs to improve obesity and hyperlipidemia by regulating the gut microbiota. Decreases in serum TC, TG, and HDL have been reported to be related to increased gut microbiota richness [ 46 ], which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These studies suggest the potential for RBPs to improve obesity and hyperlipidemia by regulating the gut microbiota. Decreases in serum TC, TG, and HDL have been reported to be related to increased gut microbiota richness [ 46 ], which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 93%
“…The gut microbiome has critical roles in protecting human health and preventing metabolic diseases [ 46 ]. Studies showed that the body weight of germ-free recipient mice is affected by the microbiota of different mice (obese or lean mice), confirming that the gut ecosystem plays a critical role in weight management [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The active compounds in Chinese torreya nut seeds can help improve cardiovascular health by reducing blood pressure, decreasing cholesterol levels, improving blood flow, reducing plaque accumulation in arteries, and preventing blood clots and may be used for the prevention and treatment of hyperlipidemia, coronary artery disease, and enhancing immune function (Xiao et al, 2022). However, it is still unclear what effect Chinese torreya nuts have on the regulation of specific hormones and reproductive-related aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Oil extracted from Chinese torreya nut contains a high proportion of unsaturated fatty acids, including oleic acid and linoleic acid (Zhang et al., 2022), which have been shown to have various health benefits, such as reducing inflammation, improving lipid profiles, and preventing cardiovascular disease. The active compounds in Chinese torreya nut seeds can help improve cardiovascular health by reducing blood pressure, decreasing cholesterol levels, improving blood flow, reducing plaque accumulation in arteries, and preventing blood clots and may be used for the prevention and treatment of hyperlipidemia, coronary artery disease, and enhancing immune function (Xiao et al., 2022). However, it is still unclear what effect Chinese torreya nuts have on the regulation of specific hormones and reproductive‐related aspects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being widely consumed as edible nuts, Torreya grandis has also been considered as a highly nutritious and health-promoting edible oil source in China [ 5 , 9 , 10 ]. Therefore, previous studies have mainly focused on the extraction, processing, and utilization of oil from Torreya grandis seeds, which leads to the inevitable production of many by-products such as the aril, seed coat, and meal during the processing of Torreya grandis [ 7 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%